2015
DOI: 10.1088/1748-6041/10/3/035008
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-conjugated alginate multilayered microspheres for controlled release of bFGF

Abstract: In order to effectively immobilize and control release of basic fibroblast growth factor (bFGF) from alginate microspheres, heparin-conjugated alginate (H-Alg) was first synthesized by covalent binding. Then multilayered H-Alg microspheres (multilayered microspheres) were fabricated via an electrostatic droplet generation technique followed by a layer-by-layer (LbL) self-assembly technique. Several techniques such as Fourier transform infrared spectroscopy (FTIR), (1)H-NMR, zeta potential analysis and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…To account for the higher surface‐area‐to‐volume ratio in the microsphere system, we also deposited two bilayers of HA‐CS to ensure uniform coverage before deposition of Hep and BMP‐2. In fact, it has been reported that this method of coupling proteins by LbL assembly can not only effectively decrease the diffusion of factors through layers, but also prolong their half‐life and maintain their bioactivity …”
Section: Resultsmentioning
confidence: 99%
“…To account for the higher surface‐area‐to‐volume ratio in the microsphere system, we also deposited two bilayers of HA‐CS to ensure uniform coverage before deposition of Hep and BMP‐2. In fact, it has been reported that this method of coupling proteins by LbL assembly can not only effectively decrease the diffusion of factors through layers, but also prolong their half‐life and maintain their bioactivity …”
Section: Resultsmentioning
confidence: 99%
“…− at 1010 cm −1 , symmetrical stretching of SvO in NH-SO 3 − at 1220 cm −1 , N-H bending at 1420 cm −1 , CvO stretching at 1610 cm −1 and OH stretching at 3400 cm −1 . 46 Most of these peaks were found in both the PA-H-PLCL and CL-H-PLCL samples; however, in contrast to PA-H-PLCL, the chemically crosslinked CL-H-PLCL exhibited a new peak at 1640 cm −1 that was characteristic of the amide bond created as a result of the covalent crosslinking between heparin and aminated PLCL. Our data are consistent with an earlier report by Singh et al, who observed a similar peak after chemical crosslinking of heparin and PCL.…”
Section: Heparinizationmentioning
confidence: 94%
“…Diffusion of the growth factors through the clusters may be inhibited due to the high polymer density, explaining why even though the gel disintegrates, the release profile is very slow. Synthesis of Alg-Hep conjugation of heparin to alginate was performed following the literature 42 with some modifications. To minimize hydrolysis of EDC, the reaction was carried out in a 0.1 M buffer of 2-morpholinoethane sulfonic acid (MES buffer).…”
Section: Kinetics Of Vascular Endothelial Growth Factor (Vegf) Releasementioning
confidence: 99%